2010
DOI: 10.1016/j.bbmt.2009.12.057
|View full text |Cite
|
Sign up to set email alerts
|

Prochymal Improves Response Rates In Patients With Steroid-Refractory Acute Graft Versus Host Disease (SR-GVHD) Involving The Liver And Gut: Results Of A Randomized, Placebo-Controlled, Multicenter Phase III Trial In GVHD

Abstract: CD127 expression on CD8 + T cells, consistent with their rapid clonal expansion and differentiation. Multiplexed Luminex cytokine analysis demonstrated high-level secretion of IL-18 and IL-1RA, with no increased secretion of TNF, IL-1b or IL-17 despite severe GvHD.The four treated recipients demonstrated rapid donor engraftment, but, unlike the controls, they were significantly protected against clinical and immunologic GvHD: They displayed neither the skin rash nor the profuse diarrhea noted in the control an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
109
3
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(117 citation statements)
references
References 0 publications
4
109
3
1
Order By: Relevance
“…Although the primary end point in that study was not achieved for the whole group of patients, there was a significant benefit over placebo group in the liver and GI tract. 41 Response rate in our cohort of patients is also similar to that reported by Introna et al 20 in a cohort of 12 pediatric patients; that study demonstrated an overall response of 66.7%. However, in their patient cohort, only 25% of the patients exhibited aGvHD over grade III, whereas in our series, 96% of the patients exhibited aGvHD grade III or IV.…”
Section: Discussionsupporting
confidence: 78%
“…Although the primary end point in that study was not achieved for the whole group of patients, there was a significant benefit over placebo group in the liver and GI tract. 41 Response rate in our cohort of patients is also similar to that reported by Introna et al 20 in a cohort of 12 pediatric patients; that study demonstrated an overall response of 66.7%. However, in their patient cohort, only 25% of the patients exhibited aGvHD over grade III, whereas in our series, 96% of the patients exhibited aGvHD grade III or IV.…”
Section: Discussionsupporting
confidence: 78%
“…32 A large randomized phase III trial involving 244 patients with steroid-refractory GVHD revealed a trend in favor of the addition of MSCs to the salvage regimen in the per protocol population in comparison with placebo (CR 40 vs 28%; P ÂŒ 0.08). 33 Taken together, in the absence of convincing results from randomized phase III trials, it seems that there is no salvage treatment for steroid-refractory GI aGVHD with obviously outstanding efficacy. Therefore, secondary criteria might be considered when choosing the therapeutic regimen.…”
Section: Discussionmentioning
confidence: 99%
“…26 The anticipation of using BM-MSCs as GVHD treatment dramatically declined in the scientific community when the negative results of the randomized clinical trial by Osiris Therapeutics were released. 27 BM-MSC administration for treatment of GVHD did not improve long-term survival 23 and have also failed to show effects on GVHD in animal models. [28][29][30][31][32] Some studies from academic institutions have shown positive results, but there is most likely a selection bias in the literature as negative results are seldom published.…”
Section: Introductionmentioning
confidence: 99%